Sphere of returning human potential: homeostatic mechanisms of threats overcoming on the way of its development (Economics and region, 2018)
The essence of human potential is revealed as the main source of economic growth, its place and role in ensuring the country’s social and economic development and increasing its competitiveness are distinguished. The features of the formation of human potential in modern conditions are highlighted. A problem approach to overcoming negative factors and threats to the development of human potential is suggested. Human potential as a collection of knowledge, experience, creative abilities, abilities of specific individuals is characterized not only by the real degree of intellectual development of society, but also by hidden opportunities, the ability to further develop spiritual production, an effective solution of socio-economic, cultural, scientific and technical and other problems. Now, unfortunately, Ukraine inefficiently uses human potential, as evidenced above all by indicators of its socio-economic development. Our country on these indicators is significantly behind the countries of Western Europe. For example, per capita GDP in Ukraine is 25 times less than, for example, in Denmark. And this negatively affects the state of human potential and its reproduction. And, as statistics show, the economic situation depends to a large extent on the quality of human potential. World practice shows that without active implementation of transformational reforms in the economic sphere, it is impossible to achieve positive shifts in overcoming challenges and threats in the way of the formation and development of the sphere of human potential reproduction. Therefore, the aim of our study is to substantiate ways and mechanisms aimed at overcoming possible challenges, threats to develop the sphere of human potential reproduction. A high degree of risk and lack of guarantees for investors on their invested funds serve as deterrents to Ukraine's economic development, and the formation of a new quality of people's life should become the main mechanism for ensuring long-term self-sufficiency and competitiveness of our country in modern conditions
Keywords: human potential; innovative activity; socio-economic development; reproduction; labor force